Improvement of Quality of Service Parameters in Dynamic and Heterogeneous WBAN - Madhumita Kathuria; Sapna Gambhir (IAES Indonesian Section, 2016)
With growth in population and diseases, there is a need for monitoring and curing of patients with low cost for various health issues. Due to life threatening conditions, loss-free and timely sending of data is an essential factor for healthcare WBAN. Health data needs to transmit through reliable connection and with minimum delay, but designing a reliable, and congestion and delay free transport protocol is a challenging area in Wireless Body Area Networks (WBANs). Generally, transport layer is responsible for congestion control and reliable packet delivery. Congestion is a critical issue in the healthcare system. It not only increases loss and delay ratio but also raise a number of retransmissions and packet drop rates, which hampers Quality of Service (QoS). Thus, to meet the QoS requirements of healthcare WBANs, a reliable and fair transport protocol is mandatory. This motivates us to design a new protocol, which provides loss, delay and congestion free transmission of heterogeneous data. In this paper, we present a Dynamic priority based Quality of Service management protocol which not only controls the congestion in the network but also provides a reliable transmission with timely delivery of the packet.